Rekaman Video CCTV (Close Circuit Television) dalam Pembuktian Acara Pidana - Nita Anggraeni (Al-Mizan (e-Journal), 2016)
The raising of technology is unvoidable in change of human civilization. That influence in various aspect, and also in law enforcement. In the past, thief can only stealling gods by bring something unlawfull, definition of gods just limited for something can touch or see, with direct manner. In digital era thief not only can steal gods by direct manner but also with the other one, they have just only â€œclickedâ€ one of the button, and get money or gods by break the account of the bank by use internet access ,we called cyber cryme. Currently with the murder of using cianida toxic, the expert witness talk about cctv evidence, the one agree and the other one disagree put in evidence categorie. In this era, need electronic evidence. Law of criminal procedure not recognize electronic evidence . that was not accordance with circumstance. uu ite recognize the digital evidence that permitted use in the other procedure law.